Clinico-Biochemical Parameters, Treatment, and Prognostic Indicators of Peritonitis in Buffaloes - Hussain, Syed Ashaq; Uppal, S.K.; Sood, N.K.; Randhawa, C.S.; Mahajan, S.K. (Journal of Buffalo Science, 2022)
Background: The present study aimed to describe clinical findings, hemato-biochemical changes, response to medical treatment, and outcomes for buffaloes suffering from peritonitis. Another objective of this study was to determine the prognosis of the disease. Methods: The study was conducted on 25 buffaloes suffering from peritonitis and presented to the Large Animal Hospital of Guru Angad Dev Veterinary and Animal Science University, Ludhiana, Punjab, India. The buffaloes were subjected to detailed clinical examination. Hematological, biochemical, and peritoneal fluid analysis was carried out along with treatment. Results: Peritonitis was more prevalent in pregnant buffaloes, being septic peritonitis in 60% of cases. The important clinical findings were depression, anorexia, reduced water intake, scanty feces, dehydration, and absence of rumen motility. The hematological findings were hemoconcentration, left shift, and toxic changes in neutrophils. Biochemical analysis revealed increased total bilirubin, AST, ALP, GGT, glucose, triglycerides, BUN, creatinine, lactate, fibrinogen, and rumen chloride, whereas albumin, fibrinogen ratio, potassium, chloride, calcium, and phosphorus were decreased. Abnormal peritoneal fluid changes were altered physical parameters and the presence of degenerated neutrophils, bacteria, and gut contents. Nucleated cell count and total peritoneal fluid protein were not reliable indicators of peritonitis. The absence of rumen motility, marked left shift, toxic changes in neutrophils, higher BUN, lower potassium (≤3.6 mmol/L), and unfavorable peritoneal fluid changes were the negative prognostic signs. Treatment with broad-spectrum antibiotics and supportive therapy led to a recovery in about 50 percent of cases, with diffuse peritonitis cases being unresponsive. Long time survival rate was good, and there was no recurrence. Conclusion: The prognosis of peritonitis in buffaloes has to be precisely assessed on the basis of clinical, hemato-biochemical, and peritoneal fluid alterations. Standard classification of transudate and exudate did not apply in the majority of buffaloes with peritonitis.